2012
DOI: 10.1111/j.1467-8535.2012.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing asynchronous online discussion environments: Recent progress and possible future directions

Abstract: Asynchronous online discussion environments are important platforms to support learning. Research suggests, however, threaded forums, one of the most popular asynchronous discussion environments, do not often foster productive online discussions naturally. This paper explores how certain properties of threaded forums have affected or constrained the quality of discussions, and argues that developing alternative discussion environments is highly needed to offer better support for asynchronous online communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 55 publications
5
98
0
2
Order By: Relevance
“…Rollag and the recommendations by Gao et al proved ODF as an important as a testing components for using effective way for strategies and combination of techniques [11] [12].…”
Section: Literature Surveymentioning
confidence: 99%
“…Rollag and the recommendations by Gao et al proved ODF as an important as a testing components for using effective way for strategies and combination of techniques [11] [12].…”
Section: Literature Surveymentioning
confidence: 99%
“…Despite these affordances, it can be challenging to create and sustain focused, in-depth online discussions (Gao et al, 2013). In a literature review, Hew et al (2010) identified several reasons why students do not fully participate in online discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the asynchronous nature of the discussions, participants have more time to think before responding, and the act of writing elicits the formation of new knowledge and ideas (Hew, Cheung & Ng, 2010). In addition, discussion forums provide a permanent space for the participants to return to their original contributions, promoting reflection (Hew et al, 2010) and self-assessment (Gao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many tools available to be integrated into collaborative learning environments for knowledge construction (Dawley, 2009;Gao, Zhang, & Franklin, 2013;Kimmerle, Moskaliuk, Oeberst, & Cress, 2015;Lan, Tsai, Yang, & Huang, 2012), microblogging tools such as Twitter have gained mounting popularity and attention (Gao, Luo, & Zhang, 2012;Ricoy & Feliz, 2016;Shabgahi, Shah, & Cox, 2013;Tang & Hew, 2017). Microblogging is a type of lightweight online application that allows a burst of multimedia content to be published and shared with others worldwide on the web (Java, Song, Finin, & Tseng, 2007).…”
Section: Introductionmentioning
confidence: 99%